2023
DOI: 10.3748/wjg.v29.i20.3203
|View full text |Cite
|
Sign up to set email alerts
|

Global research trends on diet and nutrition in Crohn’s disease

Abstract: BACKGROUND Crohn’s disease represents a challenge for patients concerned with the modified diet regimen as well as practitioners who seek the best nutritional therapy. Crohn’s disease can alter the body’s ability to digest food and to absorb nutrients, resulting in severe vitamin deficiencies, malnutrition and sometimes life-threatening complications. However, a comprehensive bibliometric analysis is lacking to map the current links between nutrition and Crohn’s disease in terms of the number of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…The United States administration has adequate resources with strong collaboration and partnerships, making it the worldwide leader in food and nutritional research [ 32 , 65 , 66 ]. This article found that the USA is the most productive country regarding malnutrition and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The United States administration has adequate resources with strong collaboration and partnerships, making it the worldwide leader in food and nutritional research [ 32 , 65 , 66 ]. This article found that the USA is the most productive country regarding malnutrition and CKD.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation test revealed a robust correlation coefficient ( r = 0.982), and the statistical significance ( P < 0.001) emphasized the precision of the search query. This dual-method approach aimed to confirm the absence of false-negative outcomes, drawing inspiration from established bibliometric studies[ 31 , 36 , 39 - 41 ].…”
Section: Methodsmentioning
confidence: 99%
“…The data collected served as the basis for generating the following information[ 32 , 49 , 50 ]: (1) Comprehensive analysis and trends of global contributions in publications regarding dialysis and depression from 1970 to 2022; (2) examination of scientific research productivity and collaboration patterns by country; (3) evaluation of research productivity among the most prolific institutions; (4) identification of funding agencies involved; (5) determination of the journals in which international researchers published their work; and (6) assessment of the citations received by these publications.…”
Section: Methodsmentioning
confidence: 99%